BISINDO Alphabet Visualization in Interactive Media - Rizky Alfi Randa; Yeffry Handoko Putra (ARTic, 2021)
Learning technology continues to develop along with the times. In the implementation of daily learning, we often encounter the utilization of technological developments in the world of education, as is often done by teachers or lecturers, namely combining technological tools in learning processes. The development of science and technology has a positive impact with the increasingly open and spread of information and knowledge from and to the whole world penetrating the boundaries of space and time. One of the technological developments in education is interactive media, with the making of this interactive learning media the teaching and learning process becomes effective, interesting and fun for students. The purpose of this research is to produce BISINDO learning media. The benefits of this learning media are to be a solution to the learning process that is effective, interesting and more fun and facilitates the learning process of students. Keywords: BISINDO; Dale’s Cone Experience; Deaf; Distance Learning Media; Sign Language